miRNA therapeutics in cardiovascular diseases: promises and problems - Nouraee, Nazila; Mowla, Seyed J. (Frontiers in Genetics, 2015)
miRNAs are a novel class of non-coding RNAs which found their way into the clinic due to their fundamental roles in cellular processes such as differentiation, proliferation and apoptosis. Recently, miRNAs have been known as micromodulators in cellular communications being involved in cell signaling and microenvironment remodeling. In this review, we will focus on the role of miRNAs in cardiovascular diseases (CVDs) and their reliability as diagnostic and therapeutic biomarkers in these conditions. Cardiovascular diseases comprise a variety of blood vessels and heart disorders with a high rate of morbidity and mortality worldwide. This necessitates introduction of novel molecular biomarkers for early detection, prevention or treatment of these diseases. miRNAs, due to their stability, tissue-specific expression pattern and secretion to the corresponding body fluids, are attractive targets for cardiovascular-associated therapeutics. Explaining the challenges ahead of miRNA-based therapies, we will discuss the exosomes as delivery packages for miRNA drugs and promising novel strategies for the future of miRNA-based therapeutics. These approaches provide insights to the future of personalized medicine for the treatment of cardiovascular diseases.